Acceptability, feasibility, and accuracy of blood-based HIV self-testing: A cross-sectional study in Ho Chi Minh City, Vietnam - Bao Vu Ngoc; Mohammed Majam; Kimberly Green; Ton Tran; Minh Tran Hung; Anh Luong Que; Diep Bui Ngoc; Chuong Hoang Le Duy (Public Library of Science (PLoS), 2023)
HIV self-testing (HIVST) is an effective approach to increase testing uptake. While oral fluid-based HIVST has been rapidly scaled, use of blood-based HIVST remains limited. We evaluated the acceptability, feasibility, and accuracy of blood-based HIVST among lay users in Ho Chi Minh City (HCMC), Vietnam. We conducted a cross-sectional study among HIV testing clients at the HCMC Pasteur Institute from March 2019 to October 2020. Participants received one HIVST kit and performed the test in front of an observer. The observer used product-specific questionnaires to collect information on the HIVST process, test results, experiences. The participants' interpretations of HIVST results were compared to health staff's interpretations and gold standard laboratory EIA reference tests. Of 2,399 participants who accepted HIVST, 64.7% were men, 62.1% aged 25-49 years, 53.5% had a higher education level, 41.4% were employed, and 35.6% were first-time testers. The vast majority (94.4%) desired to use the test in the future, and 93.9% reported willingness to recommend the test. The majority (90.8%) of participants successfully completed the self-test. One factor associated with successful completion was higher education level (aOR = 1.85; 95% CI: 1.32-2.61); while participants self-testing with SURE CHECK (aOR = 0.21; 95% CI: 0.12-0.37), INSTI (aOR = 0.23; 95% CI: 0.13-0.39), and BioSURE (aOR = 0.29; 95% CI: 0.17-0.51) or being unemployed, retired, or doing housework (aOR = 0.45; 95% CI: 0.25-0.82) were less likely to perform the test successfully. Agreement of positive and negative HIVST results as interpreted by participants and health staff was high (98.1% and 99.9%, respectively). Sensitivity and specificity of the evaluated HIVST were 96.43% (95% CI: 93.62-99.23) and 99.9% (95% CI: 99.75-100), respectively. Our findings confirm that blood-based HIVST is highly acceptable, feasible, and accurate. This evidence informs scale-up of HIVST to increase uptake of essential HIV prevention and treatment services.